GAMBARAN SANITASI SARANA PRODUKSI DAN PERSONAL HIGIENE KARYAWAN DI INDUSTRI RUMAH TANGGA PANGAN MI LETHEK “X” DUSUN BENDO TRIMURTI SRANDAKAN BANTUL TAHUN 2022 - anis safety; Agus Kharmayana Rubaya; Sigid Sudaryanto (Poltekkes Kemenkes Yogyakarta, 2022)
The Sanitation Food Home Industry Production facilities are objects of an application to maintain the safety of food products. The food poisoning cases reported by BPOM in 2019 on average occurred because household food processing did not implement good food production methods. The purpose of this study was to determine the sanitary picture of production facilities and personal hygiene of employees at IRTP Mi Lethek